Agrivoltaic approach in improving soil resistivity in large scale solar farms for energy sustainability - Ya'acob, M. E.; Lu, Li; Zulkifli, S. A.; Roslan, N.; Ahmad, W. F. H. Wan (Elsevier, 2023)
Recently, approaches have been established to improve the grounding system performance, especially with the increasing numbers of large-scale solar (LSS) PV farms. Soil resistivity is one of the contributing factors to the inefficiency of power generation as it induces high impedance on electricity flow from the source to highly sensitive PV equipment and devices such as inverters. Some critical issues on nutrient leaching derived from ammonium sulphate fertilizer direct to ground soil are the focal point of this work with the fact that soil resistivity value is inversely proportional to increasing soil salt content. Therefore, a low grounding system could be obtained with a high Electrical Conductivity (EC) and high soil moisture content. In this work, a conceptual setup for an agrivoltaic condition with 500 units of herbal crops has been cultivated directly underneath 1 PV string in Puchong Solar Farm, Selangor, Malaysia. The amount of salt or nutrient under this condition was measured leaching approximately 40 mL per polybag as means of ground treatment to improve soil resistivity value, thus indirectly reducing the risk of electrical damage. The agrivoltaic approach has shown that it can improve the performance of a grounding system in an LSS PV farm with a significant reduction of 4.45Ω earth resistance on average.